Determinants of Continuance Intention to Use a Hospital Information System in a Public Hospital in Sichuan, China - Gou, Wei (Scholar: Human Sciences, 2026)
Purpose: This study aimed to identify the determinants of Factors affecting continuance intention to use the hospital information system in a public hospital in Sichuan, China: an integration of TAM, ISS, and UTAUT. With the rapid development of the economy, informatization has emerged as a pioneering endeavor, influencing all aspects of life, including the medical field. Hospitals, as the main carriers of healthcare, have undergone significant transformations through the deep integration of traditional medical care and information technology. Research Design, Data, and Methodology: Under the continuous promotion of hospital information systems, the disadvantages caused by their usage have also received more and more attention. Integrating the different perspectives of the users, the system, and the organizational management can help analyze the important factors that affect the users' continuance intention. 506 questionnaires were collected online, and the structural equation model (SEM) was used for data analysis. Results: The results suggest that information quality, facilitating conditions, and perceived usefulness can significantly influence continuance intention, while self-efficacy negatively affects continuance intention. Conclusions: This research provides solid evidence for the validity of the integrated ECM, ISS, and SCT model in the hospital in the model formation system field, which can be a theoretical basis for enhancing medical efficiency.